Strangers and scapegoats: extending God's welcome to those on the margins - Vos, Matthew (Baker Academic, 2022)
A Christian sociologist explains how the problem of the stranger lies at the root of many problems humanity faces, such as racism, sexism, and nationalism, but an identity in Christ frees us to love strangers as neighbors and friends.